Three new species of squat lobsters of the genus Munidopsis Whiteaves, 1874, from Guadeloupe Island, Caribbean Sea (Crustacea, Decapoda, Munidopsidae) - Rodríguez-Flores, Paula C.; Macpherson, Enrique; Machordom, Annie (Zootaxa, 2018)
The genus Munidopsis is one of the most diverse genera within squat lobsters. Here, three new species of Munidopsis, M. cornuata n. sp., M. senticosa n. sp., and M. turgida n. sp., from <500 m off Guadeloupe Island (Caribbean Sea), are fully described and illustrated. Among the Atlantic species of the genus, M. cornuata n. sp. belongs to the group of species having the dorsal surface of the carapace with spines and is most similar to M. robusta (A. Milne-Edwards, 1880), from the Gulf of Mexico and Caribbean Sea. Munidopsis senticosa n. sp. resembles M. barbarae (Boone, 1927) from the Bahamas and the Gulf of Mexico and M. penescabra Pequegnat & Williams 1995, from off Georgia and Gulf of Mexico; the three species belong to the group having the carapace covered with sharp spines. Finally, M. turgida n. sp. is characterized by having the dorsal surface of the carapace, abdomen and pereiopods covered by granules; and resembles M. granulens Mayo, 1972, from NW Caribbean Sea. Apart from the morphological evidence, the analysis of mitochondrial genes (COI and 16S) supports establishing these new species, showing very high genetic divergences compared to their congeners (from 14.5 to 17% for COI, and 7.7 to 12.8% for 16S data).